COVID-19 in Coincidence with Transient Distal Renal Tubular Acidosis in an Infant - Seyedeh-Kiana Razavi-Amoli; Hamid Mohammadjafari; Daniel Zamanfar; Mohammad Reza Navaeifar; Zahra Sadati-Lamradi; Mohammad Sadegh Rezai (Case Reports in Infectious Diseases)
Background. Post-COVID-19 nephropathies have been reported profusely in the literature with diverse pathophysiological mechanisms. To the best of our knowledge, this is the first report of transient distal (type 1) renal tubular acidosis (dRTA) in an infant with confirmed COVID-19. Case Presentation. We describe a 32-day-old female with diarrhea and fever without respiratory complaints. Her weight, height, and head circumference were normal for age. The primary lab test showed leukocytosis, neutrophilia, elevated inflammatory markers, and non-anion-gap metabolic acidosis. Real-time polymerase chain reaction (RT-PCR) and elevated SARS-CoV-2 immunoglobulin M confirmed COVID-19, while echocardiography and spiral chest computed tomography scan were normal. Intravenous fluid therapy and supportive care were initiated. Blood culture was positive for Klebsiella pneumoniae. Amikacin and cefotaxime were ordered. Although diarrhea and dehydration gradually improved, venous blood gas still showed metabolic acidosis. Due to the alkaline urine and hypokalemic-hyperchloremic metabolic acidosis, dRTA was diagnosed. Notably, the patient dramatically responded to Shohl’s solution. Conclusions. Regarding the various manifestations of COVID-19, the possible association between dRTA and COVID-19 needs further investigation in children.